Memoria en la neblina. Los orígenes chinos de la familia Yeckting en el Perú - Yeckting Vilela, Fabiola (2020)
This paper is a journey through personal and family memory that gathers information, testimonies and interviews about the chinese origin of the author’s last name. As the starting point, the migration of her great-grandfather is presented, then the social life of three generations is explored in order to identify the roots and identity that the Yeckting family has inherited and still preserves in current times.